Clinical profile of severe acute malnutrition among children under five years of age living in Bundelkhand region of Uttar Pradesh - Chaurasiya, Om Shankar; Pathak, Ram Kumar; Gupta, Sapna; Chhabra, Kawalpreet (Indian Journal of Child Health, 2018)
Introduction: Malnutrition is a general term and often refers to undernutrition resulting from inadequate consumption, poor absorption, or excessive loss of nutrients, but the term also encompasses overnutrition. Objective: The objective is to study the clinical profile of children with severe acute malnutrition (SAM) and also to assess the effectiveness of Nutrition Rehabilitation Center in providing therapeutic care for children with SAM. Materials and Methods: This prospective study was conducted at the department of pediatrics of a tertiary care center at Jhansi for a period of 12 months among 152 children with SAM. A detailed history and physical examination finding were recorded in pretested pro forma at the time of admission using the standard methodology and anthropometric measurement expressed in standard deviation from the median of the reference population (WHO). Results: Majority of the patients (96, 63.15%) belonged to age group of 6